A Novel TBX19 Gene Mutation in a Case of Congenital Isolated Adrenocorticotropic Hormone Deficiency Presenting with Recurrent Respiratory Tract Infections - Akcan, Nese; Serakıncı, Nedime; Turkgenc, Burcu; Bundak, Ruveyde; Bahceciler, Nerin; Temel, Sehime G. (Frontiers in Endocrinology, 2017)
Introduction: Congenital isolated adrenocorticotropic hormone deficiency (CIAD) is a rare disease characterized by low adrenocorticotropic hormone (ACTH) and cortisol levels. To date, recurrent pulmonary infections in infancy have not been reported as an accompanying symptom of CIAD. Case Presentation: A 7-year-old boy was hospitalized nine times for recurrent lower respiratory tract infections. The results of all tests for the possible causes of wheezing were within the normal limits. His ACTH and cortisol levels were persistently low. All other pituitary hormone levels, and adrenal ultrasound and pituitary magnetic resonance imaging results, were normal. Molecular analyses confirmed the diagnosis of CIAD by identifying compound heterozygosity for two mutations in the TBX19 gene. The first was a novel frameshift c.665delG variant in exon 4 of TBX19 gene, leading to premature termination that was predicted to result in a non-functional truncated protein. The second was a nonsense C-to-T transition in exon 6 of the TBX19 gene, resulting in an arg286-to-ter mutation (dbSNP: rs74315376). Both parents were heterozygous for one of the mutations. Conclusions: Here, we presented a new mutation in the TBX19 gene in a patient with CIAD who presented with recurrent respiratory tract infections. This expands the mutation spectrum in this disorder. To conclude, adrenal insufficiency should be considered in patients with unexplained recurrent infections to prevent a delay in diagnosis. Keywords: Adrenal insufficiency; adrenocorticotropic hormone; cortisol; respiratory infections; TBX19 gene